Pelatihan Digital Marketing Untuk Mengoptimalkan Pemasaran Produk UMKM Masyarakat Desa Guntung - Edi Setiawan; Sumardi Sumardi; Elmy Nur Azizah; Cici Tania; Fikri Hidayat (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
In the business world, marketing or marketing is one of the important things that must be done. In line with the development of existing technology, strategies in doing marketing have also begun to change in a more modern direction. The community that is the main subject is the Guntung village community where the number of people who need training is 20 people. People still do not understand in doing digital marketing so that products are less known to people outside the region because products are only marketed by word of mouth method. So, to optimize marketing, digital marketing training is needed to increase people's understanding of digital marketing. Thus, the goal to be achieved in this activity is to train the community to master marketing techniques through social media and internet networks through the creation of interesting content with digital marketing facilities in order to generate significant income to improve the economy of the people of Guntung Village, Koba District - Central Bangka. The approach technique is carried out by training and simulation methods directly using computer devices and devices from each participant. With this real work lecture, it can open the horizons of the people of Guntung Village, Koba District - Central Bangka.